Discharged but detained: analysis of an aspect of patient rights in Nigeria (2011)
A normal hospital practice is the discharge of patients from admission after due care. What is not normal is the post-discharge detention of a patient in the hospital by hospital authorities because of inability to pay hospital bills. This practice is common in Nigeria, but the hierarchies of the health and justice sectors tend to "look the other way". Healthcare providers are often faced with a dilemma between two issues: observing the oath to "do no harm" even after the period of care, as may be suggested by the unlawful post-discharge detention of a client; and ensuring that there is continuous finances to sustain health services for the common good. Issues raised here include, the physician/patient relationship; patient's rights versus that of the healthcare providers; accessibility and availability of healthcare. The key players in this scenario are the physician/hospital management; the nurses and the patients. This paper examined the judicial and human rights implications involved and provide suggestions for striking a balance between the rights of the patient and the duty/right of the healthcare providers. In doing this, the healthcare policy in Nigeria, vis-a-vis its accessibility, affordability and availability are examined